Polymorphisms and high on-aspirin platelet reactivity after off-pump coronary artery bypass grafting. (August 2013) - Wang, Zanxin; Gao, Fei; Men, Jianlong; Yang, Jie; Modi, Paul; Wei, Minxin
Abstract: Objectives . High on-aspirin residual platelet reactivity (RPR) after coronary artery bypass grafting (CABG) is a transient phenomenon with important implications for graft patency. This study was designed to determine the role of polymorphisms [TBXA2R (T924C), GPIIIa (Pl A1/A2 ), P2Y1 (A1622G), and GP1Bα (C1018T)] on RPR in Chinese patients undergoing off-pump CABG (OPCAB). Methods. Of 420 patients recruited to this study, 210 patients underwent primary OPCAB and 210 controls with ischemic heart disease received optimal medical therapy. Arachidonic acid-induced platelet aggregation and urinary 11-dehydro thromboxane B2 were measured at baseline and following aspirin administration on days 1, 4, 10, and on 6th month. Four polymorphisms were identified [TBXA2R (T924C), P2Y1 (A1622G), Pl A1/A2 and GP1Bα (C1018T)]. Results. On the first post-operative day, 62 patients (29.5%) were with high RPR and 148 (70.5%) were with low RPR. Of the former, 33 (15.7%), 10 (4.6%), and 0 (0%) patients remained with high RPR on days 4, 10, and on 6 month, respectively. No individuals with high RPR was found in controls. Logistic regression identified TBXA2R-924TT (OR = 4.5; 95% CI, 1.8–11.1) and body mass index > 27 kg/m 2 (OR = 2.73; 95% CI, 1.1–7.0) as independent risk factors for high on-aspirin RPR. Conclusions. High on-aspirin RPR after OPCAB is associated with genetic polymorphism TBXA2R-924TT and obesity.